(untitled) (London Journal of Engineering Research, 2023)
Staircases connect the floors of multi-storey buildings and pedestrian bridges. There are different types of stairs, such as straight stairs, straight stairs with intermediate landings, curved stairs, L-shaped stairs, etc. The study focused on straight staircases with a central beam supporting the stairs as a double cantilever. The study of structural systems is relatively rare. There are four loading cases that we examine; the first is a live load on one side of the staircase, the second is a live load on both sides of the staircase, the third is a time history of three earthquakes, and the fourth is a dynamic load of pedestrians. A major objective of this study was to establish equations for estimating the central beam’s internal forces.